Analisis Kadar Iodium Pada Terasi Yang Diperdagangkan Di Pasar Pa’baeng-Baeng Kota Makassar - Zuhra Nurul; Ardiansah Hasin; Hijral Aswad (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2018)
The research is motivated because shrimp paste is one of the processed food products that has a fairly complete nutritional content, especially the iodine content contained in the raw material itself both from fish and shrimp. The purpose of this study is to find out how much iodine levels in shrimp paste using the spectrophotometric method, this research is experimental with a purposive sampling technique. Based on the results of examination of iodine content analysis of 4 shrimp paste samples carried out at the Pharmacy Instrumentation Laboratory of the Faculty of Pharmacy, University of East Indonesia Makassar and analyzed by qualitative and quantitative tests it can be concluded that there were differences in the results of the four samples where samples A = 0.078 ppm or mg / g, sample B = 0.084 ppm or mg / g, sample C = 0.088 ppm or mg / g, and sample D = 0.085 ppm or mg / g and these results indicate iodine presence in all four shrimp paste samples. The conclusion of this study is that there is a difference in iodine levels from the four shrimp paste samples with a value of iodine content which is low compared to the normal value determined by SNI at 30-80 ppm or mg/g.